Effect of Monovalent Ion Parameters on Molecular Dynamics Simulations of G-Quadruplexes - Havrila, Marek; Stadlbauer, Petr; Islam, Barira; Otyepka, Michal; Šponer, Jiří (Journal of chemical theory and computation, 2017)
G-quadruplexes (GQs) are key noncanonical DNA and RNA architectures stabilized by desolvated monovalent cations present in their central channels. We analyze extended atomistic molecular dynamics simulations (∼580 μs in total) of GQs with 11 monovalent cation parametrizations, assessing GQ overall structural stability, dynamics of internal cations, and distortions of the G-tetrad geometries. Majority of simulations were executed with the SPC/E water model; however, test simulations with TIP3P and OPC water models are also reported. The identity and parametrization of ions strongly affect behavior of a tetramolecular d[GGG]4 GQ, which is unstable with several ion parametrizations. The remaining studied RNA and DNA GQs are structurally stable, though the G-tetrad geometries are always deformed by bifurcated H-bonding in a parametrization-specific manner. Thus, basic 10-μs-scale simulations of fully folded GQs can be safely done with a number of cation parametrizations. However, there are parametrization-specific differences and basic force-field errors affecting the quantitative description of ion-tetrad interactions, which may significantly affect studies of the ion-binding processes and description of the GQ folding landscape. Our d[GGG]4 simulations indirectly suggest that such studies will also be sensitive to the water models. During exchanges with bulk water, the Na+ ions move inside the GQs in a concerted manner, while larger relocations of the K+ ions are typically separated. We suggest that the Joung-Cheatham SPC/E K+ parameters represent a safe choice in simulation studies of GQs, though variation of ion parameters can be used for specific simulation goals.
Keywords: kationty jednomocné; Guanine; DNA; simulace molekulární dynamiky; G-kvadruplexy; sodík; Nucleic Acid Conformation; draslík; Sodium; Water; Cations, Monovalent; guanin; RNA; Molecular Dynamics Simulation; Potassium; voda; G-Quadruplexes; konformace nukleové kyseliny